PENGARUH PEMBELAJARAN DEEP LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of Realistic Mathematics Education-based Deep Learning on elementary school students’ mathematical critical thinking skills. This study applies a quantitative approach through a one-group pretest-posttest design. A total of 24 fifth-grade students at Pasirtalaga 1 Elementary School were involved as research participants. Data collection was carried out through a test designed to measure students’ mathematical critical thinking skills. Data analysis was carried out using descriptive statistics, normality tests, paired sample t-tests, and N-Gain calculations. The results of the analysis indicate the development of mathematical critical thinking skills with an N-Gain score of 0.73, which is classified as high. This aspect indicates that Realistic Mathematics Education-based deep learning has a positive effect on students’ mathematical critical thinking skills.